Effect of sodium ascorbate on the tensile bond strength of an adhesive system to sodium hypochlorite-treated dentin - Deauna, Junia Mae B.; Tanyag, Crisostomo Ibarra C.; Segarra, Armin G. (Co-author).; Faustino, Maria Karla T. (Adviser).
Endodontically treated restored with posts and core materials are cemented by resin-based adhesives. These materials prevent microleakage and improve the longevity of the restoration by enhanced retention. However, Sodium Hypochlorite, the most common irrigant used in endodontic treatment causes a decrease in bond strength of resin cements. Several studies have used Sodium Ascorbate, a neutral and biocompatible agent to reverse the effects caused by Sodium Hypochlorite. This study investigates the capability of Sodium Ascorbate to counter act the effects of Sodium Hypochlorite on a pulpal dentin surface. Sixty sectioned bovine teeth blocks were randomly assigned to three groups. The surface treatment for each group is shown in the table below. After undergoing surface treatments, the composite blocks were bonded to the dentin blocks with Adper? Easy One (3M (ESPE) Self-Etch Adhesive. The Shimadzu Universal Testing machine with a crosshead speed of 1mm/min was used to measure the Tensile Bond Strength (TBS) of each specimen. One-way ANOVA followed by Multiple Comparison Post Hoc test using Turkey's Honest Difference test were utilized for statistical analysis. The results are shown in the table below. Therefore, the researchers, based on the results gathered, have concluded that 10% Sodium Ascorbate has no significant effect on the tensile bond strength of a Self Etch Adhesive system on a 1% Sodium Hypochlorite-treated dentin.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental materials